Efficacy of a Motorized Mechanical Oscillator in Abdominal Fat, Weight, and Waist Circumference Reduction - Two Case Studies: 動力化機械擺動瘦身器在減少腹部脂肪、體重和腰圍的效力 - 二個專題研究 - ANG, Chloe; KOH, Teik Hin (Asian Journal of Physical Education & Recreation, 2006)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The importance of reducing health risk associated with high abdominal fat is frequently emphasized. Consequently, in Singapore, we have witnessed good sales on motorized mechanical oscillators touted to induce slimming based on the principles of acupressure. However, to date, no study has been done to evaluate the efficacy of such equipment. This pilot study aims to examine the efficacy of motorized mechanical oscillators in reducing waist circumference, weight and abdominal fat percentage over 4 weeks as well as augment the data on acupressure for weight reduction. Two male subjects, one mildly overweight and the other severely overweight, were recruited. They were required to keep to their existing lifestyles and dietary habits and were instructed to wear the oscillator belt for 30 minutes each time, twice a day, as per instructions given in the manual. The machine was operated using the automatic mode. The results show a slight decrease in total body fat % ascertained by DEXA scans. There was also a reduction in waist circumference and an increase in lean mass in the trunk area in both subjects. Specifically, one participant (mildly overweight) lost 1.2% of total body fat, and 0.7cm on the waist girth but gained 1 kg of lean trunk mass. The other participant (severely overweight), although having lost only 0.2% of total body fat and 1.3cm on the waist girth, lost 1.7 kg in total body weight. He also gained in trunk lean mass that resulted in trunk fat reduction of 0.4%. There appears to be some success in such treatment modality particularly with regard to reducing abdominal fat. Certainly, more work needs to be done and future studies are being considered that will involve bigger sample sizes. 調查顯示腹部脂肪的累積能引起健康危害，因此減少腹部脂肪的重要性需要廣泛重視的。在新加坡，瘦身產品如動力化的機械擺動瘦身帶都獲得非常好的銷售額。此瘦身帶是以穴位理療原理為依據而設計開發的。可是至今，這類產品的瘦身效果還沒得到科學證明。這項中間試驗的目的是研究在超過4個星期的時間裏，這類瘦身帶對減少腰圍，體重和腹部脂肪的百分數效果；同時也希望增添用穴位理療原理在減肥方面的資料。在二位男性患者當中，一位屬於輕微超重，而另一位屬於嚴重超重。在這項中間試驗調查中，二位患者接受了為期四周的治療療程。療程包括每日使用本瘦身帶二次，一次療程三十分鐘。除此以外，患者需要保持原本的生活方式和飲食習慣。並遵循指導手冊方法操作。此瘦身帶的操作是採用自動化的方法。由DEXA結果顯示二位元患者的脂肪都有顯微的下降，腰圍也有所減小，並且腹部的肌肉有明顯的增加。其中一位患者(輕微肥胖者)的脂肪減少了1.2%，腰圍減少了0.7公分，而肌肉增加了1公斤。第二位患者的身體脂肪減少了0.2%，腰圍減少了 1.3公分，體重也減輕了1.7公斤。同時肌肉也增加了，這使到他的腹部的脂肪減少了0.4%。由此可見，這類瘦身方法對減少腹部脂肪似乎有效。所以，這方面的調查和研究需要更多的工作。接下來希望進行更廣泛，更大規模的研究。